2013
DOI: 10.1016/j.anbehav.2013.03.038
|View full text |Cite
|
Sign up to set email alerts
|

The height of choosiness: mutual mate choice for stature results in suboptimal pair formation for both sexes

Abstract: Animal Behaviour 86 (2013) 37e46 * Based on Fowler-Finn & Rodríguez (2012a, b). y In the speed-dating literature often referred to as 'selectivity' or 'choosiness'.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
54
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 36 publications
(63 citation statements)
references
References 40 publications
7
54
2
Order By: Relevance
“…Reasons that height would likely impact fighting ability include its relationship to arm reach, leg length and hence speed, and leverage. Empirically, it is known that height is highly related to female mate choice such that taller men are universally seen as more attractive (Stulp et al 2013), though it is not clear that this is because of height's role in fighting as opposed to it being an indicator of energy reserves, immune system competence, or other qualities important to mate choice mechanisms. There is also a pronounced sexual dimorphism in height with men being on average about five inches taller than women, and many such sex differences are likely combat adaptations (see Sell, Hone & Pound 2012).…”
Section: Section 5: Discussion Of Height and Flexed Biceps Circumferencementioning
confidence: 99%
“…Reasons that height would likely impact fighting ability include its relationship to arm reach, leg length and hence speed, and leverage. Empirically, it is known that height is highly related to female mate choice such that taller men are universally seen as more attractive (Stulp et al 2013), though it is not clear that this is because of height's role in fighting as opposed to it being an indicator of energy reserves, immune system competence, or other qualities important to mate choice mechanisms. There is also a pronounced sexual dimorphism in height with men being on average about five inches taller than women, and many such sex differences are likely combat adaptations (see Sell, Hone & Pound 2012).…”
Section: Section 5: Discussion Of Height and Flexed Biceps Circumferencementioning
confidence: 99%
“…It is also the case that selection pressures on height can differ between the sexes, where sexual selection via female choice exerts more of an influence on male height than does male choice of female partners (for further discussion of these points, see [3]). This is not to say that height does not influence female mating success, only that the effects are known to be stronger in males (see [17,49] and [3,16] for reviews). Indeed, there is a striking similarity between the selection pressures identified in this study, and relationships found between height and attractiveness in both laboratory and field settings [3,16,17], where taller men and average height women are, on average, preferred by the other sex.…”
Section: Discussionmentioning
confidence: 99%
“…This is not to say that height does not influence female mating success, only that the effects are known to be stronger in males (see [17,49] and [3,16] for reviews). Indeed, there is a striking similarity between the selection pressures identified in this study, and relationships found between height and attractiveness in both laboratory and field settings [3,16,17], where taller men and average height women are, on average, preferred by the other sex. Thus, direct preferences for taller height among men, and a combination of preference for average height and life-history trade-offs among women may account for the patterns seen here.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Taller women may be perceived to be more dominant than shorter women (Boyson, Pryor, & Butler, 1999), have higher social esteem and higher incomes (Judge & Cable, 2004), and be more satisfied with their height (Lever, Frederick, Laird, & Sadeghi-Azar, 2007). In one speed dating study, although women preferred men who were 25 cm taller on average, men preferred women who were only 7 cm shorter on average (Stulp, Buunk, Kurzban, & Verhulst, 2013). Based on these findings, one might expect that taller women might have more mating opportunities, but it is difficult to make any a priori predictions regarding the links between height and sexual history for women.…”
Section: Preferences For Female Heightmentioning
confidence: 99%